2023
DOI: 10.3389/fonc.2022.1102392
|View full text |Cite|
|
Sign up to set email alerts
|

Label-free LC-MS/MS proteomics analyses reveal CLIC1 as a predictive biomarker for bladder cancer staging and prognosis

Abstract: IntroductionBladder cancer (BC) is a significant carcinoma of the urinary system that has a high incidence of morbidity and death owing to the challenges in accurately identifying people with early-stage BC and the lack of effective treatment options for those with advanced BC. Thus, there is a need to define new markers of prognosis and prediction.MethodsIn this study, we have performed a comprehensive proteomics experiment by label-free quantitative proteomics to compare the proteome changes in the serum of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 58 publications
0
2
1
Order By: Relevance
“…Precursor-exhausted CD8+ T cells typically lack effector molecules for tumor cell cytotoxicity, while terminally exhausted cells release cytokines for tumor killing but express high levels of immune checkpoints such as PD-1 ( 39 ). In contrast to Wang’s findings ( 36 ), we speculate that the upregulation of PD-L1 induced by high DARS2 expression may weaken the cytotoxicity of CD8+ T cells against tumor cells. Our experiments, involving DARS2 knockdown and overexpression, confirm concurrent upregulation or downregulation of PD-L1 with DARS2.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Precursor-exhausted CD8+ T cells typically lack effector molecules for tumor cell cytotoxicity, while terminally exhausted cells release cytokines for tumor killing but express high levels of immune checkpoints such as PD-1 ( 39 ). In contrast to Wang’s findings ( 36 ), we speculate that the upregulation of PD-L1 induced by high DARS2 expression may weaken the cytotoxicity of CD8+ T cells against tumor cells. Our experiments, involving DARS2 knockdown and overexpression, confirm concurrent upregulation or downregulation of PD-L1 with DARS2.…”
Section: Discussioncontrasting
confidence: 99%
“…In studies of bladder cancer prognostic markers, Wang found that CLIC1, as a prognostic marker, showed a negative correlation with CD8+ T cells. Patients with low CLIC1 expression exhibited increased infiltration of CD8+ T cells, correlating with a better prognosis ( 36 ). However, our study revealed that in patients with high DARS2 expression, there is an increased infiltration of CD8+ T cells, but paradoxically, a worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that CLIC-1 may play a role in the distant spread of cancer cells, as well as in the proliferation and migration of tumor cells. The study conducted by Wang et al [12] clearly establishes a positive correlation between the stage of bladder tumors and the in-creased level of CLIC1. Our research aimed to investigate the activity of CLIC-1 in the tissues of patients diagnosed with bladder tumors who underwent TURBT surgery at our clinic.…”
Section: Resultsmentioning
confidence: 86%
“…Previous research has shown that CLIC1 and CLIC3 are closely associated with tumor cell proliferation, apoptosis, and migration, and play a crucial role in tumor formation and development. Limited studies have shown that CLIC1 and CLIC3 levels increase significantly in advanced stages of bladder tumors, at both serum and gene levels [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Further PPI networks for all the differentially expressed proteins using STRING database version 11.5 were constructed. 22 …”
Section: Methodsmentioning
confidence: 99%